PENGELOLAAN ARSIP DINAMIS PADA BAGIAN BARANG MILIK NEGARA (BMN) UNIVERSITAS SEBELAS MARET SURAKARTA - Fina Prasetyani; Patni Ninghardjanti; Tutik Susilowati (JIKAP (Jurnal Informasi dan Komunikasi Administrasi Perkantoran), 2022)
The purpose of this study was to determine (1) the management of dynamic archives at the BMN UNS office; (2) Problems that arise; and (3) Efforts are made to overcome the problems that arise. This research is a case study qualitative research, with primary data sources from observations and interviews with BMN office employees, for secondary data from field documentation. The sample uses the snowball sampling technique that the researcher assigns one of the BMN employees as a key informant then asks for advice from other informants related to research. Data analysis used in this research interactive data analysis techniques in three stages, namely data reduction, data presentation, and drawing conclusions. The results show (1) the management of dynamic archives at the BMN office includes the creation of archives, the use of archives, maintenance and security of archives, shrinkage and destruction of archives; (2) Obstacles in the form of the absence of experts in the field of archives, lack of understanding of archives, lack of socialization of the archive management system, and the classification of types of letters that are still lacking in detail; (3) Efforts to overcome these obstacles include appointing a special employee who handles archives, attends training, socializes the results of the training, and if no appropriate letter classification is found, the closest classification is entered.